1978
DOI: 10.1126/science.663616
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Development and Social Policy

Abstract: The city of Warsaw was razed at the end of World War II and rebuilt under a socialist government whose policy was to allocate dwellings, schools, and health facilities without regard to social class. Of the 14,238 children born in 1963 and living in Warsaw, 96 percent were given the Raven's Progressive Matrices Test and an arithmetic and a vocabulary test in March to June of 1974. Information was collected on the families of the children, and on characteristics of schools and city districts. Parental occupatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 8 publications
1
25
0
Order By: Relevance
“…Equalizing socioeconomic environments does little or nothing to reduce the dispersion in IQ, as was illustrated by the great variation in intellectual capacities among children born in post-WWII Warsaw despite the city's Communist government providing the same (integrated) housing, medical care, and other amenities to all inhabitants (Firkowska et al, 1978).…”
Section: Intelligence and Health Inequality 19mentioning
confidence: 99%
“…Equalizing socioeconomic environments does little or nothing to reduce the dispersion in IQ, as was illustrated by the great variation in intellectual capacities among children born in post-WWII Warsaw despite the city's Communist government providing the same (integrated) housing, medical care, and other amenities to all inhabitants (Firkowska et al, 1978).…”
Section: Intelligence and Health Inequality 19mentioning
confidence: 99%
“…In a study carried out in communist Poland in 1974, substantial social class differences in intelligence were reported in a sample of approximately l4,000 11 year olds in Warsaw (almost all the children in the city) (Firkowska, Ostrowska, Sokolowska, Stein, Susser, & Wald, 1978). The authors concluded that "an egalitarian social policy executed over a generation failed to override the association of social and family factors with cognitive development that is characteristic of more traditional societies".…”
mentioning
confidence: 96%
“…and academic achievement (8,12,24,26,33,34,37,40). The degree of the association varies between a correlation of 0.35 to 0 .5 depending on the study and whether it focuses on achievement test scores or educational attainment (24).…”
Section: Discussionmentioning
confidence: 99%
“…T he importance of the family to children's academic performance is well documented in numero us studies (2,4,12,20,21,24,30,31) showing that a large proportion of children who fail in school are from disadvantaged families. The period of most rapid rate of growth of intelligence and achievement occurs during the first few years of life (3), when the family's influence is paramount.…”
mentioning
confidence: 97%
See 1 more Smart Citation